PEMIMPIN MADRASAH DALAM PERSPEKTIF AL-QUR’AN HADITS - yaqien, nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
There are various requirements in becoming the leader of madrasa in Islam, such as the existence of justice, honesty, resposibility, emphaty, and so fort, which are pertinent to the expert theories about leadership. It is preferrable that the leader of madrasah come from generous generation because, indirectly, it affects the leadership quality of the leader. Once a person become a leader in madrasa, he must be able to perform very well because it means that he deal with responsibility in the world and in the hereafter. Rasulullah saw. saw forbade people to ask to be a leader, especially when they do not own most leadership aspects. If people insist for that responsibility, Allah swt might will not bless that job, and futhermore, there might be bad things happen in the future, such as students’ failure in national examination, lack of school achievement, lack of society reliance, and so forth. These might be happen since basically, Allah swt will not help people who ask for position.Keyword: Leader, Madrasa, Alquran, Hadits